How Does Green Human Resource Management Improve Sustainable Organizational Performance in Public Services? - Astuti, Sih Darmi; Riyanto, Fery; Demircioglu, Aytekin (Universitas Muhammadiyah Yogyakarta, 2023)
Research Aims: The issues, such as global warming, increasing levels of pollution, increasing carbon, and climate change, make it mandatory for all organizations to strive to preserve the environment and work for the welfare of society. The aim to be achieved in this study was to explore the practice of green human resource management (GHRM) and its contribution to increasing sustainable organizational performance (SOP) through green service innovation (GSI) in the local government organizations of Semarang City, Indonesia.Design/Methodology/Approach: This research used a quantitative method. The data in this study were collected using closed online questionnaires for the leaders of the civil servants in each regional government organization in Semarang City. The data analysis employed the Structural Equation Model-Partial Least Square (SEM-PLS) utilizing the software of Smart PLS 3.Research Findings: The results of the data analysis demonstrated that all proposed hypotheses were accepted. It has been proven that GHRM and GSI could, directly and indirectly, improve SOP in Semarang City Government through the primary indicator of the vision of developing environmental management and services for the community and environmentally friendly digital service innovations.Theoretical Contribution/Originality: GSI could mediate the relationship between GHRM and SOP. In addition, this study revealed that the digital elements of public services in GSI enormously increased SOP.Practitioners/Policy Implications: The results have been good news for leaders in public service organizations with different policies on becoming sustainable organizations and preserving environmentally friendly practices in serving the community.Research Limitations/Implications: The authors recognize that the current study has limitations. This research only focused on organizational performance. Since the authors see that GHRM and GSI practices play a decisive role for employees, this study recommends further research to investigate the role of GHRM and GSI on employee performance.